Low-RCS reflectarray with phase controllable absorptive frequency-selective reflector - Huang, Hao (2021)
This paper presents a methodology to control the reflection phase response from a 3-D bandstop structure backed with an absorbing material. An absorptive frequency-selective reflection structure using the cascaded arc-shaped strip resonators and absorbers is utilized to obtain an absorption-reflection-absorption response. The reflection phase response of the structure within the reflection band is then flexibly controlled by top-loaded metallic patches with variable size. An application of this methodology is demonstrated by designing a high-gain and low-radar cross section (RCS) reflectarray. The in-band phase profile of the reflecting surface is constructively designed to collimate the beam in the far field. Meanwhile, the out-of-band scattering from the planar reflector is significantly reduced. Compared with a conventional reflectarray, the radiation performance of the proposed antenna is maintained with an aperture efficiency of 50.1% and directivity of 23.5 dBi. Significant RCS reduction has been achieved with a fractional bandwidth of 76.9% and 17.1% for the lower and upper bands with reduction levels of 10 and 8 dB, respectively.